SOCIAL ENGINEERING THROUGH EDUCATION LAW - Saifuddin Dhuhri (PETITA: JURNAL KAJIAN ILMU HUKUM DAN SYARIAH, 2019)
Studies on art education and culture are a continuing concern within academicians and politicians. Although extensive research has been carried out on the fields, few studies exist, which concern about the use of art education for cultural hegemony. This study concerns about Acehnese culture and identity. During the time of colonisation, imperialist scholar; Snouck Hurgronje had used cultural resources as the instrument to instil false cultural identity for the interest to take control over Aceh. Stepping on the Dutch’s colonialising policies, the central government of Indonesia has, as argued, used art curriculum as a hegemonic media for similar interests. This article discusses the case of art education in Acehnese by analysing the content of the text books recommended by the central government. This work is to demonstrate the representation of Acehnese cultural identity in the “Art and Culture” curriculum of schools in Aceh. I employ Freire, Hall, Apple, and Giroux thoughts to formulate the framework of this article. The aim of this paper is to understand the mechanism of the art curriculum used to nationalise local people and to uncover the scheme of cultural hegemony in Acehnese schools, Indonesia. This work significantly contributes toward understanding the relation between cultural hegemony and education. Abstrak: Penelitian tentang pendidikan seni dan budaya menjadi perhatian dari kalangan akademisi dan politisi terus menerus. Meskipun penelitian terkait telah banyak dilakukan di lapangan, studi yang menyangkut penggunaan pendidikan seni untuk hegemoni budaya masih terbatas. Penelitian ini membahas tentang budaya dan identitas Aceh. Selama masa penjajahan, sarjana imperialis; Snouck Hurgronje menggunakan sumber daya budaya sebagai instrumen untuk menanamkan identitas budaya yang salah demi kepentingan untuk mengendalikan Aceh. Dalam kebijakan kolonialisasi Belanda, pemerintah pusat Indonesia juga menggunakan kurikulum seni sebagai media hegemonik untuk kepentingan yang sama. Artikel ini membahas tentang pendidikan seni di Aceh dengan menganalisis isi buku teks yang direkomendasikan oleh pemerintah pusat. Penelitian ini adalah bertujuan untuk menunjukkan representasi identitas budaya Aceh dalam kurikulum “Seni dan Budaya” di sekolah-sekolah di Aceh. Saya menggunakan pemikiran Freire, Hall, Apple, dan Giroux untuk merumuskan kerangka artikel ini. Tujuan artikel ini adalah untuk memahami mekanisme kurikulum seni yang digunakan untuk menasionalisasi masyarakat lokal dan mengungkap skema hegemoni budaya pada sekolah-sekolah di Aceh, Indonesia. Tulisan ini memberikan kontribusi yang signifikan terhadap pemahaman hubungan antara hegemoni budaya dan pendidikan. Kata kunci: Hukum pendidikan, Hegemoni, Pendidikan Seni, Identitas Aceh